Analisis Biaya Produksi dan Pendapatan Budidaya Ikan Patin (Pangasius pangasius) di Kabupaten Kapuas - Lukas Lukas (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2012)
Research on the analysis of production costs and income of patin fish (Pangasius pangasius) farming in Kapuas Regency, aims to determine how the influence of production costs partially or individuals on income patin fish. The research method is a simple probability sampling with random sampling and interview. The results of the study since the year 2008-2011 showed that patin fish production levels affect the patin fish farmers' income and the presence of a strong relationship and a positive correlation between production costs and revenues.